Extracting metal ions from water with redox active biopolymer electrodes1. Issue 3 (15th May 2015) - Admassie, Shimelis; Elfwing, Anders; Skallberg, Andreas; Inganäs, Olle
<x xml:space="preserve">Abstract</x> Lignin which is a renewable, environmentally friendly and cheap material is investigated as a promising material for use in energy storage and waste-water treatment technologies.